2012
DOI: 10.5560/znb.2012-0093
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of the Triaminoguanidinium Ion, 1. Synthesis, Crystal and Molecular Structures of 1,2,3-Tris(benzylamino)guanidinium Salts

Abstract: Triaminoguanidinium chloride was transformed into 1,2,3-tris(benzylamino)guanidinium chloride (3-Cl) in two steps. Anion exchange allowed the preparation of further salts 3-X. The crystal and molecular structures of 3-Cl, 3-I, 3-CF 3 COO and 3-CF 3 SO 3 were determined. It was found that both the conformation of the cation and the nature of the anion determines the packing in the solid state. Interestingly, three different conformations of the cation were observed in the crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Furthermore it should be recalled, that certain 1,2,4,5-tetrazinanes were found to have useful analgesic and antiinflammatory activities [26] and some dihydrotetrazine derivatives [27], in contrast to substituted 1,2,4,5-tetrazinanes [28], exhibited strong antitumor effects. [9] were prepared as reported. Hydrazin-1-yl)-3,3-dimethyl-2,3,4 A chromatographic column (l = 50 cm, diameter 5 cm) was charged with a strongly basic anion exchanger (type III, OH form, Merck Supelco, 4.0 g) dispersed in water (50 mL).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore it should be recalled, that certain 1,2,4,5-tetrazinanes were found to have useful analgesic and antiinflammatory activities [26] and some dihydrotetrazine derivatives [27], in contrast to substituted 1,2,4,5-tetrazinanes [28], exhibited strong antitumor effects. [9] were prepared as reported. Hydrazin-1-yl)-3,3-dimethyl-2,3,4 A chromatographic column (l = 50 cm, diameter 5 cm) was charged with a strongly basic anion exchanger (type III, OH form, Merck Supelco, 4.0 g) dispersed in water (50 mL).…”
Section: Resultsmentioning
confidence: 99%
“…NMR monitoring revealed that a stepwise dehydrogenation of the three PhCH 2 -NH groups of 10 took place, which finally resulted in tris(benzylidenamino)guanidine 13. The latter can be obtained more conveniently by deprotonation of N,N′,N″-tris(benzylidenamino)guanidinium chloride 14 (which is in fact the direct synthetic precursor of 3-Cl [9]). A crystal structure determination confirmed the identity of 13 (Fig.…”
Section: Reaction Of Nn′n″-tris(benzylamino)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the past two decades, ionic liquids (ILs) have attracted much attention and were proposed for a broad range of applications in various areas of natural and engineering sciences . Guanidinium ions constitute a new class of ionic liquids used for various applications . Some authors including one of us have systematically synthesized many hexaalkylguanidinium ionic liquids to investigate their fundamental physicochemical properties as well as to investigate the application to electrochemistry including the development of lithium‐ion batteries .…”
Section: Introductionmentioning
confidence: 99%